At the Southern limit: the Arenal Central site and the Guaraní occupation of the Paraná Delta (Argentina) - Loponte, Daniel; Carbonera, Mirian; Schneider, Fernanda; Machado, Neli; Bertoncello, Aline; Szczygel, Maicon Telles; Acosta, Alejandro; Mazza, Barbara; Alí, Sheila; Capparelli, Isabel (Frontiers in Environmental Archaeology, 2025)
This study analyzes the archaeological record of Arenal Central, a Guaraní residential site on Martín García Island within the Río de la Plata estuary, situated in the southernmost region colonized by these Amazonian populations. It presents data on technology, subsistence, procurement networks, catchment areas, stylistic behaviors, and chronology, providing five new radiocarbon dates that make this site the best-dated Guaraní context in the region, and the second Guaraní residential base analyzed for this area. The results are integrated with previously known data to examine key aspects of Guaraní colonization, including chronology, subsistence strategies, resource acquisition, hunting ranges, and settlement spatial distribution, contributing to a new synthesis of Guaraní archaeology at the southernmost extent of their expansion in South America. Finally, the findings are contextualized within the broader framework of human occupations in insular settings.